The EFFECT OF COMPENSATION AND WORK ENVIRONMENT ON LOYALTY THROUGH MOTIVATION AS AN INTERVENING VARIABLE AT THE REGIONAL SECRETARIAT OF JEMBER REGENCY - Heni Rosianti; Nursaid Nursaid; Ni Nyoman Putu Martini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of compensation and work environment on the loyalty of Jember Regency Regional Secretariat employees, both directly and through work motivation as an intervening variable. The phenomenon of declining ASN loyalty due to low motivation, perception of unfair compensation, and suboptimal working conditions is the background of the research. A quantitative approach is used through surveys and Partial Least Square (PLS) analysis. The results of the study show that compensation and work environment have a positive and significant effect on work motivation, and directly increase employee work loyalty. In addition, work motivation has been shown to significantly mediate the influence of compensation and the work environment on loyalty, suggesting that motivation is an important psychological factor in strengthening the relationship between organizational rewards and employee loyalty. These findings indicate that the increase in ASN loyalty does not only depend on financial aspects, but is also influenced by the perception of fairness, comfort of the work environment, and motivational encouragement from leaders. Therefore, local governments need to implement fair compensation policies, create a healthy and collaborative work environment, and strengthen employee motivation through a sustainable performance coaching and reward system